A Research of Intrusion Detection System in General as Well as Snort in Detail Before Introducing it into Global Cyber Soft Company - Pasha, Mohamed Aly (International Journal For Research In Advanced Computer Science And Engineering, 2022)
Nowadays, with the expanding of Internet all over the world, many hackers who try to steal some confident information to use for their own benefit or just destroy or modify it. From this, IDS/IPS (intrusion detection/prevention system) was born to help users, companies or institutions to detect and prevent this issue. My company currently is considering to install an intrusion detection system and this thesis is aim to study IDS in general to get the common knowledge and Snort in detail for our managers make a decision to implement it or not. In this Master’s thesis, I will cover two main parts: the first one includes of an intense research study about the IDS/IPS and comparing the differences between them. Subsequently, we will continue this part with some limitation points where IDS/IPS still needs to be checked and show up some requirements for the better intrusion detection system.Second part of the thesis would try to show how to configure of Snort in Windows environment. Some demo of attacking on the environment where Snort is installed will be performed in order to show its protection on reality. Finally, we will evaluate some advantages and disadvantages compared to other software to conclude whether we should implement it on our company or not.